Cross layer schemes for QoS provisioning in mobile communication networks : - Abd El-atty, Saied (2008)
Concluding, our study was mainly focused on WCDMA based 3G and beyond networks and how to develop cross-layer mechanisms for QoS provisioning. Firstly, we propose a cross-layer framework for efficient packet scheduling procedure in WCDMA-based networks. At the medium access control (MAC) layer, we perform a prediction of the future state of the wireless channel for each user by utilizing information from the physical layer. The prediction criterion is based on the signal-to-interference ratio (SIR) measurements of the received signal at each mobile user; we then employ a finite state Markov chain (FSMC) model for predicting the future state of the wireless channel. According to this prediction we define which users should be served by the packet scheduler during the next frame. The main idea of the scheduling scheme is to prioritize the connections not only according to their delay sensitivity, but also according to the predicted state of their wireless channel during the next frame.Next we propose radio resource management scheme as an effective combination of a call admission control (CAC) mechanism together with a traffic scheduling algorithm. These two schemes are designed and operated in a complementary fashion in order to support QoS provisioning for handover (HO) calls in WCDMA systems. The CAC mechanism is based on a guard code scheme in WCDMA system which employs orthogonal variable spreading factor (OVSF) codes as channelization codes. The guard code scheme reserves some code capacity to favor the continuation of handover (HO) calls over the new calls. However, during the handover procedure the HO calls experience high delays as a number of packets have to be forwarded through the wireline infrastructure to the target cell. Thus, we additionally employ a delay-aware traffic scheduler namely delay driven scheduler (DDS) at the MAC layer which aims to prioritize calls which experience high delays such as HO calls. Furthermore, DDS is able to exploit information from the physical layer in order to avoid erroneous packet transmission and increases system performance. Finally, we propose an improved channel quality information (CQI) reporting scheme which aims to reduce the required CQI signaling overhead in high speed packet access (HSPA) systems by exploiting a CQI prediction method. According to this scheme, Node B predicts all the intermediary CQI reports between two subsequent CQI reports by utilizing a FSMC model of the wireless channel. The main benefit of the proposed scheme is the decrease of the uplink interference and thus the improvement of the uplink reception quality at the negligible cost of slight reduction of the efficiency of Node B scheduling procedure.